PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN SRAGEN - Kurniawan, Hutomo; Aji, Ambyah Atas (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2022)
This study aimed to determine work motivation, work discipline, and job satisfaction for the performance of district service employees partially and simultaneously. This study used a sample of 40 respondents. The sampling technique used is jenuh sampling or census where the sampling technique that takes all members of the population as a sample. A questionnaire is an instrument used to collect data. The test data in this study are validity, reliability, multiple linear analysis of the f test, t test and coefficient of determination. The data is processed using SPSS version 16. The results of the study found tcount > ttable calculation (4,150 > 2,028) and a significant value of 0.000 < 0.05. This means that work motivation has a positive and significant effect on the performance of District Service employees. tcount work discipline calculation > ttabel (4,887 > 2,028) and a significant value of 0.000 < 0.05. This means that work discipline has a positive and significant effect on the performance of District Service employees. thitung job satisfaction known to > ttabel (2,328 > 2,028) and a significant value of 0.022 < 0.05. This means that job satisfaction has a positive and significant effect on the performance of District Service employees. It is proven by the results of the F test that the F-value of the Fcount > Ftabel (125,053 > 2.84) and a significant value of 0.000 < 0.05 means that motivation, discipline and work satisfaction together have a positive and significant influence on the performance of district office employees.